Cognitive Behavioral Therapy pada remaja dengan gangguan depresi - Umilatul Hasanah (Universitas Muhammadiyah Malang, 2022)
The subject was an 18-year-old woman who had just graduated from vocational high school. Diagnosis of depression with symptoms of decreased interest in doing activities, no appetite, insomnia at night, but sleeping long enough during the day. Having excessive feelings of guilt and worthlessness, decreased concentration,and difficulty focusing. There is a specific plan to commit suicide with the desire to drink clothes fragrances and eat spicy food. The assessment used included interviews, observations and psychological tests, and BDI questionnaires. The intervention used to overcome the subject's problems is Cognitive Behavior Therapy (CBT). Intervention targets can change the subject's thinking about his abilities and future to be more realistic. The results of the intervention showed that CBT was effective in reducing depression in subjects. The subject can change his negative thinking regarding abilities and the future and has returned to carry out daily activities.